Investigation of a quad-band microstrip antenna using a DNG-MTM radiation patch - Yu, Chenyin (2023)
A compact quad-band microstrip antenna based on double-negative metamaterial (DNG-MTM) is proposed in this letter. To realize miniaturization and multi-band characteristics, a novel coplanar tri-band DNG-MTM unit, consisted of an epsilon negative (ENG) MTM and a mu negative (MNG) MTM, is firstly designed and employed as the antenna radiator. The antenna’s electrical dimension is 0.23λ0 × 0.37λ0, where λ0 is the free space wavelength at 3.5 GHz. The peak gain is 5.3, 6.3, 5.8, and 3.4 dBi and the radiation efficiency reaches 96%, 82%, 91% and 86% for 2.84–3.55 (22.2%), 6.6–7.18 (8.4%), 7.44–9.08 (19.9%), and 11.1–14.74 (28.2%) GHz, respectively. These four bands have effectively covered 5G (3.5-GHz), C-band, X-band, and Ku-band for satellite systems. The size of the proposed antenna has been reduced by about 55% in comparison to the traditional method.